Analisis Persepsi Masyarakat Dengan Sikap Memilih Pengobatan Tradisional Lo’i Keta Daripada Ke Rumah Sakit Di Era Pandemi Covid-19 - Junai din; Sri yuliana; Arif rahman (STIKES Citra Delima Bangka Belitung, 2021)
Covid-19 pandemic era change people’s behavior looking for alternative medicine to increase body immunity in prevention Covid-19 transmission. Lo’i Keta is tradisional medicine trusted by society as prevention and treatment various diseases and increase the body’s immunity moment Covid-19 pandemic. This research to analyze perception and people’s attitudes in choosing treatment traditional Lo’i Keta during the Covid-19 pandemic. The research is qualitative using purposive sampling. A sample of 15 participants. Results: return of behavior drug consuption traditional Lo’i Keta during the Covid-19 pandemic, for fear infected with covid in healt facilities. Lo’i Keta can be trusted increase body immunity, safe to use and easy to get by society. Utilization of Lo’i Keta trusted by society as prevention and treatment skin disease, boils (furucles), water defect (varicella) Gastritis, Liver, Cancer, Fever and increase antibody immunity. How to use Lo’i Keta that is drink, chewed and covered at the site of the disease. Usage optimazation Lo’i Keta tradisional medicine need to be tested in the laboratory to find out the content of Lo’i Keta.